Desain Lingkungan Kerja Berdasarkan Pendekatan Kesehatan dan Keselamatan Kerja - Eko Nursubiyantoro; Wahyu Wibowo Eko Yulianto (OPSI, 2019)
Kalasan Fried Chicken Industry Center is one of the home industries producing fried chicken in Yogyakarta. Initial measurements obtained from the working environment conditions of occupational health and safety are still considered to be less than comfortable and in accordance with standards. As a result of lack of lighting and high room temperature, workers often experience eye fatigue, dizziness, frequent loss of focus and poor quality fried chicken production. Occupational health and safety according to the standard, it is necessary to improve the lighting aspect with the Lumen Method (Lumen Method or Zonal Cavacity Method, ZCM), the physical environment in terms of temperature is designed by increasing the fan capacity needed by the work environment so that the number and type of fans with quality can be determined the right air for the room. The lighting needs of the work environment are 9 24 watt lights and an exhaust fan and sufficient air volume. The results of the implementation were able to increase the level of lighting and temperature in accordance with work comfort.